PSYCHOLOGICAL WELL-BEING PADA ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF - Komarudin Komarudin (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This study aim to determine the dynamics of the psychological well-being in children with special needs in inclusive schools and the factors that affect the psychological well-being in children with special needs in inclusive schools. Data collection in this study was conducted using semi-structured interview techniques. Analysis of the data used refers to the opinions of Miles and Hubermen through 3 steps, namely data reduction, data display, and conclusion drawing. The results showed that: 1) The four research subjects had independence in carrying out daily activities and had good environmental control; 2) In determining the purpose of life, the four subjects have had their dreams, but have not been able to direct them; 3) The positive relationship of the subject to others, is influenced by the response of others to the subject. If the environment conducts bullying actions on the subject, then the subject feels threatened to be in the environment; 4) Factors that affect psychological well-being subjects in inclusive schools, namely economic, social, learning systems, and subject characteristics.